Impact of Two Sport Education Units on Learning Outcomes in Primary School - Mahedero, Pilar; Calderón, Antonio; Martínez de Ojeda, Diego; Arias-Estero, José Luis (Cuadernos de Psicología del Deporte, 2022)
The purposes of the study were (a) to explore the effect of two-sport education units (basketball and floorball) on game performance and game knowledge of primary education students according to their skill level, and (b) to know whether there were differences according to the sport taught (basketball and floorball). The participants were 33 students from two primary school classes. This study followed a mixed-methods approach. Two teaching units (basketball and floorball) were applied in two different classes, one class experienced basketball and the other floorball. Quantitative data were obtained through a simple pre-experimental pretest-posttest design. We analysed game performance variables (decision making, skill execution, game performance, game involvement) and game knowledge. Students’ performance was also measured using qualitative data which were collected through two methods: (a) experts analysis on game performance of students, and (b) students’ and teacher’s perception of students´ performance with sport education. The results were affected both the sport taught and the skill level of students. The teacher emphasized that it was very complex for the primary students to understand some tactical and technical concepts, especially in floorball. At the primary level, student previous experience with the content and skill level conditioned the results in the variables related with game performance and knowledge. It is suggested that enacting sport education units of invasion games with implement such as floorball, at the primary level, might require more explicit instruction and longer teaching units in order to guarantee a minimum level of technical and tactical improvement.